2002
DOI: 10.1159/000067320
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Percutaneous Balloon Valvuloplasty and Open Commissurotomy for Mitral Stenosis

Abstract: Eighty patients with tight and pliable mitral stenosis were randomized in a prospective trial comparing percutaneous balloon valvuloplasty and open commissurotomy. Mitral valve area increased significantly in both groups immediately after the procedures. However, a decrease in mitral valve area occurred in both groups at 6, 12 and 24 months during the follow-up. There was no death in either group. Two patients had significant mitral regurgitation after percutaneous balloon valvuloplasty. After 24 months, all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 24 publications
1
20
0
2
Order By: Relevance
“…Survival in this study at the end of evolution was 95.7% in the single balloon group and 97.9% in the Inoue balloon group. Major event free survival was 82.3% in the single balloon group and 91.7% in the Inoue balloon group in comparison to the findings in literature between 16% and 90% during followup of four to twelve years [6][7][8][9][10][11][12]19,25,38,39 due to differences in the patient groups.…”
Section: Inoue Balloonmentioning
confidence: 46%
See 2 more Smart Citations
“…Survival in this study at the end of evolution was 95.7% in the single balloon group and 97.9% in the Inoue balloon group. Major event free survival was 82.3% in the single balloon group and 91.7% in the Inoue balloon group in comparison to the findings in literature between 16% and 90% during followup of four to twelve years [6][7][8][9][10][11][12]19,25,38,39 due to differences in the patient groups.…”
Section: Inoue Balloonmentioning
confidence: 46%
“…Mortality in literature ranges from zero 37 to 18% 12,[18][19][20]26,38 during followup of one to ten years and is greater in groups with higher echocardiographic scores 12,13 , reaching as high as 17% to 18% 9,18 depending on unfavorable characteristics or longer follow-up. The follow-up period for the single balloon group (54 ± 31 months) was greater than that of the Inoue balloon group (34 ± 26 months).…”
Section: Inoue Balloonmentioning
confidence: 99%
See 1 more Smart Citation
“…Dear Sir, I read with interest yet another comparative study between percutaneous balloon valvuloplasty and open commissurotomy for mitral stenosis [1]. I hope this will be the last such comparative study, because it simply confirmed five previous studies [2][3][4][5][6], all of which showed comparable results between these two methods of treatment for mitral stenosis.…”
mentioning
confidence: 69%
“…Percutaneous BMV is a good option for young women with MS, because it can lead to a substantial increase in valve area with sustained benefi t for many years [ 43 ]. Because clinical trials have found BMV to be equivalent or superior to closed surgical commissurotomy, the latter procedure largely has been abandoned [44][45][46]. Suitability for BMV is determined by valve morphology and the amount of mitral regurgitation (MR).…”
Section: Mitral Stenosismentioning
confidence: 99%